Hipnosis terapeutica - Zuñiga Calle, Manuel (Revista Universidad de Guayaquil, 1998)
Hypnosis is an artificially induced state similar to sleep. The encephalographic findings made in the psychological laboratory show that the recordings of brain waves during hypnotic and waking states are visibly similar, but show a notable difference from those recorded in the state of physiological sleep.